1996
DOI: 10.1074/jbc.271.17.10230
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Novel Human Diacylglycerol Kinase ζ

Abstract: To further explore the role of diacylglycerol metabolism in endothelial responses, we used a degenerate reverse transcription-polymerase chain reaction method to identify diacylglycerol kinase isozymes expressed by human endothelial cells. We report the isolation of a 3.5-kilobase cDNA encoding a novel diacylglycerol kinase (hDGK) with a predicted molecular mass of 103.9 kDa. Human DGK contains two zinc fingers, an ATP binding site, and four ankyrin repeats near the carboxyl terminus. A unique feature, as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
176
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(181 citation statements)
references
References 57 publications
5
176
0
Order By: Relevance
“…1, a and b), which in AtDGK2 includes amino acid residues 342-471. DGKc domains contain a presumed ATP binding site with a GXGXXG consensus sequence (where G represents glycine, and X represents any amino acid) (28). Although the presumed ATP binding site in AtDGK2 (Gly 401 -Ala 406 ) has an alanine instead of a glycine residue at the end of this motif, it is obvious from our results (see below) that this change does not render the enzyme inactive.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…1, a and b), which in AtDGK2 includes amino acid residues 342-471. DGKc domains contain a presumed ATP binding site with a GXGXXG consensus sequence (where G represents glycine, and X represents any amino acid) (28). Although the presumed ATP binding site in AtDGK2 (Gly 401 -Ala 406 ) has an alanine instead of a glycine residue at the end of this motif, it is obvious from our results (see below) that this change does not render the enzyme inactive.…”
Section: Resultsmentioning
confidence: 60%
“…Interestingly, 1,2-SAG and 1,2-DOG are more unsaturated (18:0/20:4 and 18:1/18:1 for 1,2-SAG and 1,2-DOG, respectively) than the other lipids tested. Similarly, in other studies with human DGKs, a strong preference for 1,2-SAG and 1,2-DOG was observed (28,36). Saturated diacylglycerols (1,2-DOCG, 1,2-DPG, and 1,2-DMG) or monosaturated DAG analogs (1,2-OAG) were poor substrates for AtDGK2 (Fig.…”
Section: Fig 2 Phylogenetic Analysis Of Plant Dgk Isozymesmentioning
confidence: 99%
“…The hDGKζ gene encoded for a protein of approx. 103 kDa that showed no selectivity for naturally occurring long-chain diradylglycerols [39]. However, analysis of the hDGKε cDNA showed that this sequence encoded for a 64 kDa protein that contained a DAG-binding site distinct from that found in the other DAG kinases.…”
Section: Discussionmentioning
confidence: 99%
“…The DGKδ gene was identified from a testis library and encodes a 130 kDa particulate protein that showed no DAG selectivity [37]. The other new DGK genes were isolated from human endothelial cells and were termed hDGKζ and hDGKε [38,39]. The hDGKζ gene encoded for a protein of approx.…”
Section: Discussionmentioning
confidence: 99%
“…To date, nine subtypes of mammalian DGKs have been cloned (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). All DGK isozymes consist of a conserved catalytic domain and two or three cysteine-rich C1 domains designated as C1A, C1B, and C1C (16).…”
mentioning
confidence: 99%